Social Welfare in China: The role of equity in the transition from egalitarianism to capitalism - Koen Rutten (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2010)
The 'Scientific Development Concept', promulgated by Hu Jintao in 2007 articulated the increased eminence of social development in official ideology. The shift from political and economic objectives towards social factors can be explained by growing concerns over the current negative externalities of China's economic growth, the long and midterm sustainability of its economic development model and the implications thereof for social stability and political legitimacy. An immediate priority has been to formulate and implement a response to mitigate the disruptive effects of the transition to a market economy. Such a response must cover a wide array of social issues, ranging from provision of health, education and infrastructure, pension to unemployment insurance and poverty alleviation. The welfare issue is characterized by high degrees of complexity and interdependency between endogenous factors and exogenous political and economic variables. Improvements are further confounded by the high decentralization of administration, regional disparities and the sheer size of operations. Although progress has been made on most fronts, it remains to be seen whether recent initiatives will prove sufficient to meet China's social challenges. In this paper, I provide a summary of the academic literature on post-reform development of the welfare system. I will give an overview of its most salient problems, initiatives and their preliminary outcomes. Finally, I will present some concluding remarks and provide suggestions for future research.
hdl:10398/8018
Keywords: 330; China; Social Welfare; Economic Transition; Rural-Urban Dichotomy; Equality; Sozialer Wandel; Soziale Sicherheit; Sozialpolitik; Systemtransformation; Stadt-Land-Beziehungen; Bibliometrie; China